Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil Dan Menengah (SAK-EMKM) Pada Usaha Mikro Kecil Menengah (UMKM) Berkah Laundry - Sari, Atika (Jurnal Akuntansi Syariah (JAkSya), 2021)
The problems discussed in this study are the recording of financial statements of MSME Berkah Laundry which have not recorded in detail and are not in accordance with applicable accounting standards, namely SAK-EMKM. The purpose of this research is to prepare financial reports based on SAK-EMKM. The type of research that the author uses is field research with a descriptive qualitative approach. The data collection technique that the author uses is through interviews with the owners of the Berkah Laundry UMKM and documents related to the preparation of the Berkah Laundry UMKM financial statements. And the purpose of this research is to compile financial reports on UMKM Berkah Laundry based on SAK-EMKM. The results showed that the financial statement recording system carried out by the Berkah Laundry UMKM based on SAK-EMKM had three components of financial statements, namely the statement of financial position with total assets of Rp. 45,222,375,00 and total equity and liability of Rp. 45,222,375,00, income statement with total profit of Rp. 7,602,375,00 and notes to financial statements.